The prognostic value of inflammation markers in postoperative gliomas with or without adjuvant treatments. Issue 25 (25th June 2021) - Luo, Yuanfu; Deng, Renzhi; Zhong, Qiulu; Luo, Danjing; Li, Xiangde; Chen, Xueyuan; Tao, Sha; Feng, Zhoubin; Jiayi, Liu; Huang, Yiyun; Li, Jian; Liu, Wenqi
Abstract : Abstract: Recent studies have shown that some inflammatory markers are associated with the prognosis of solid tumors. This study aims to evaluate the prognosis of glioma patients with or without adjuvant treatment using the systemic immune-inflammation index (SII), neutrophil-to-lymphocyte ratio (NLR), and platelet-lymphocyte ratio (PLR). All patients who were diagnosed with gliomas at the first and second affiliated hospital of Guangxi Medical University between 2011 and 2020 were included in this study. The optimal cutoff value of SII, NLR, and PLR was determined by X-tile software program. We stratified patients into several groups and evaluated the progression-free survival (PFS) and overall survival (OS) of SII, NLR, and PLR during the period of pre-surgical, con-chemoradiotherapy, and post-treatments. Multivariate Cox regression analyses were performed to detect the relationships between OS, PFS, and prognostic variables. A total of 67 gliomas patients were enrolled in the study. The cutoff values of SII, NLR, and PLR were 781.5 × 10 9 /L, 2.9 × 10 9 /L, and 123.2 × 10 9 /L, respectively. Patients who are pre-SII < 781.5 × 10 9 /L had better PFS ( P  = .027), but no difference in OS. In addition, patients who had low pre-NLR (<2.9 × 10 9 /L) meant better OS and PFS. PLR after adjuvant treatments (post-PLR) was significantly higher than pre-PLR ( P  = .035). Multivariate analyses revealed that pre-SII, pre-NLR were independent prognostic factors for OS (pre-SII: HR 1.002, 95% CI: 1.000–1.005, P  = .030 and pre-PLR: HR 0.983, 95% CI: 0.973–0.994, P  = .001), while pre-PLR was an independent factor for PFS (HR 0.989, 95% CI: 0.979–1.000, P  = .041). High pre-SII or high pre-NLR could be prognostic markers to identify glioma patients who had a poor prognosis.